Enforcement of labour laws : a review, 1970-71 to 1980-81 (Govt. of N.-W.F.P., Directorate of Labour Welfare, 1982)
On the activities of the Directorate in ensuring the compliance of various industries with labor law legislation; includes staffing and budget information.